Preparasi dan Karakterisasi Komposit Kitosan-ZnO sebagai Agen Hidrofobik pada Kain Katun - Dina Kartika Maharani; Kayla Naulia Fadhila (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2022)
This study aims to make a composite material from chitosan and ZnO as well as its application as a hydrophobic agent for cotton fabrics through a chitosan-ZnO composite coating process on cotton fabrics. The manufacture of chitosan-ZnO composites used the sol-gel method with variations in the volume ratio of chitosan to ZnO, namely 7:3, 6:4, 5:5, 4:6 and 3:7. The hydrophobicity of cotton cloth coated with chitosan-ZnO composite was measured using the water contact angle (WCA) method and the highest water contact angle was 131º for the variation of chitosan: ZnO of 7:3. Characterization of chitosan-ZnO composites using FTIR and XRD instruments The FTIR results show an interaction of chitosan with ZnO, this is supported by the presence of C=O groups observed at wave numbers 1556 cm-1, C-N groups appear at 1397 cm-1 and 1338 cm-1, –OH and –NH groups are detected at 3242 cm-1, O-Zn-O bonds were identified at 425 cm-1 and also –C-O-C- bonds between the chitosan group and ZnO were seen at 1019 cm-1 and 1052 cm-1. XRD results showed peaks at 2θ 37.1º, 246.82º and 68.31º indicating the presence of a ZnO nanoparticle crystalline phase and characteristic peaks of chitosan at 2θ 10.6º and 2θ 21.8º. The results of FTIR and XRD characterization show that the chitosan-ZnO composite has been successfully synthesized. Key words: Hydrophobic, Chitosan-ZnO Composites